ANALYSIS OF DESIGNING LTE-A RELEASE 12 WITH CARRIER AGGREGATION INTERBAND TECHNIQUE ON 1800 MHz FREQUENCY AND 2300 MHz OPERATOR X IN CENTRAL SEMARANG CITY - Juwi Nanda Sinulingga; Ade Wahyudin; Muntaqo Alfin Amanaf (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2018)
Cariier aggregation (CA) is an LTE network technology - Advaced from the 4th generation network. With the CA technology it can increase the throughput value obtained by the user customers by utilizing the spectrum available. The concept of CA itself is to combine several carrier signals based on existing site data and traffic data obtained from one of the operators in Indonesia and for the measurement parameters to be analyzed RSRP, CINR and percentage of users connected based on simulation in software Atoll 3.3 For the design of LTE network release 8 or without CA signal level obtained ≥ 80 dBm of 100%, CINR level ≥ 5 dB of 88%, the average percentage of users connected 97.44% and the average throughput of 1995 Mbps.While on the network LTE release 12 with carrier aggregation interband technique obtained signal level ≥ -80 dBm 100%, CINR level ≥ 5 dB equal to 78.3%, the average percentage of user connected 99.61% and throughput 2059.14 Mbps.Based on the analysis results obtained that LTE network release 12 with carrier aggregation interband technique is better and feasible applied to meet more throughput high in Central Semarang City.